Exploring the impact of multimodal artifact creation in Canva on the understanding of multimodal texts in EFL Learners - Carcamo, Benjamin (Technology in Language Teaching & Learning, 2025)
Multimodality is an important component of the English as a Foreign Language (EFL) classroom. Among its myriad elements, one that has not been addressed in recent research is the importance of engaging in the creation of multimodal texts in EFL classes. This study investigates how adding lessons focused on the creation of multimodal texts in EFL classrooms contributes to EFL students’ understanding of multimodal texts in English. Employing a quasi-experimental design, the study involved the comparison two groups of students who learned English through a strong approach to multimodality. The control group focused only on viewing skills while the treatment group additionally engaged in artifact multimodal making through Canva in the second language. Our findings suggest that students who participated in this educational experience improved multimodal literacy, which serves as evidence in favor of the use of a strong approach to multimodality in EFL classrooms. We recommend that educational policies and teaching practices should integrate this approach to make EFL lessons a strategic support for the development of multimodal literacy.